Early Orthopedic Retraction of the Premaxilla in Bilateral Complete Cleft Lip and Palate: An Innovative Approach to a Difficult Problem. (May 2016) - Mahmood, Rizwan; Flood, Tim; Robinson, Stephen; Al-Gholmy, Mohammed
Bilateral cleft lip and palate occurs in 9.2% of cleft patients. Many approaches have been adopted to manage the protrusive premaxillary segment in patients with bilateral cleft lip and palate. Some advocate the use of intraoral appliances, occasionally combined with invasive surgery, which often requires revision at a later date. The authors describe the case of a 3-year-old child born with bilateral cleft lip and palate presenting with a protuberant premaxilla and an overjet greater than 25 mm. Prompt intervention was warranted in this case due to the potential for traumatic compromise to the dentition of the premaxillary segment and a distinct lack of social integration reported by the parents. The patient was managed with a novel, innovative approach using orthodontic traction and minimally invasive surgery. The literature has been reviewed and the patient's subsequent physiological and psychosocial development has been monitored. He has since undergone successful alveolar bone grafting.